Coupling Mechanisms Between Lower And Upper Atmosphere Through Planetary Wave Coherence: Correlation Studies - Priyanka; M Z Ansari; Rajpal (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Research into the relationship between the lower and the upper atmosphere and the feedback mechanisms which control the state of the entire atmosphere is crucial. This work aims to determine whether the planetary wave coherence could be the mechanism that mediates the connections between these atmospheric domains. In the present work we determine the correlation among wave activity at the lower and upper atmosphere based on field observational datasets. These results reveal that the behavior of planetary waves in the troposphere and the stratosphere is critically coupled with the physical processes that are simultaneously taking place in the said levels. In addition, we set some connections between coherence and seasons weather conditions. These outcomes are a reminder of the importance of planetary waves in driving atmospheric transport and the effect the associated conclusions could potentially have on weather and climate guidance. The work presented is important because it contributes to understanding communication among various aspects of the atmosphere and offers a good basis for the study of the mechanisms through which communication occurs.